Experiences of midwives and nurses when implementing abortion policies: A systematic integrative review. (August 2022) - Carvajal, Bielka; White, Helen; Brooks, Jane; Thomson, Ann M; Cooke, Alison
Highlights: Providers shape policy the implementation process. Abortion policies implementation morally challenges many providers. Midwives and nurses face multiple challenges when providing abortion care. These challenges relate to beliefs about human life, women's rights, and resources. Midwives/nurses still experience occupational stigma when providing abortion care. Abstract: Introduction: Policy implementation can be affected by what individuals believe to be right and wrong. When implementing abortion policies, providers' moral beliefs can be relevant in the success of the implementation process. Considering that midwives and nurses are direct providers of abortion care, exploring their experiences related to abortion policy implementation could provide helpful information to prevent policy failure. Methods: Systematic integrative review. The studies were identified through an electronic search strategy and the screening of the reference lists of all selected articles. Studies were retrieved from eight medical and social sciences databases. Thirty-one studies focused on midwives' and nurses' experiences of implementing abortion policies, irrespective of setting or age of study were included in this review. Studies included used qualitative, quantitative and mixed methods. Study quality was appraised using the Mixed Method Appraisal Tool version 2018. No study was excluded from this review based on its quality appraisal. Results: In terms of their quality, most studies included in this review were conducted appropriately. Three superordinate themes represent the main elements that challenge midwives and nurses when providing abortion care. The first superordinate theme identified that many midwives and nurses believed fetuses are sentient beings, making them worthy of compassionate treatment. The next superordinate theme was focused on preferences and expectations about abortion care. Finally, the third superordinate theme illustrates midwives' and nurses' experiences with other team members, highlights their creativity when challenged with insufficient resources and provides a glimpse of the numerous techniques used for coping with work-related stress. Conclusion: Midwives and nurses worldwide face multiple challenges when providing abortion care. Guidelines aiming to support policy implementation should consider how abortion affects healthcare providers and suggest appropriate measures to reduce these and other barriers. Midwives and nurses technical and ethical competencies for abortion provision should be strengthened.